2004
DOI: 10.1002/bjs.4643
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of laparoscopic versus open abdominal rectopexy

Abstract: Laparoscopic rectopexy is associated with superior clinical outcomes and is cheaper than the open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 10 publications
1
37
1
1
Order By: Relevance
“…Previous studies comparing the costs of laparoscopic and open colectomy demonstrate conflicting results [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. While the majority of these are small, retrospective cohort series, several prospective, randomized controlled trials have been performed.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies comparing the costs of laparoscopic and open colectomy demonstrate conflicting results [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. While the majority of these are small, retrospective cohort series, several prospective, randomized controlled trials have been performed.…”
Section: Discussionmentioning
confidence: 98%
“…Although operative time and cost may be increased by laparoscopic repair (LR) of rectal prolapse, the overall costs are reduced [24]. There is limited information on longterm functional results and recurrence rates.…”
mentioning
confidence: 98%
“…It shows that, with a well-trained surgeon, the laparoscopic approach is not necessarily requiring more time than open procedures [15,17]. Thus, the prolonged operative time is no longer an applicable argument against the laparoscopic approach, and it is reported that the laparoscopic approach has an overall lower cost compared with open procedures [15,18,19].…”
Section: Discussionmentioning
confidence: 97%